Pelatihan Ekspresi Sastra: Pelatihan Membaca Puisi dengan Teknik dan Intonasi Bagi Siswa Kelas VII SMP Negeri 1 Tukka,Tapanuli Tengah - -, Khairunnisah; Mariance Mila, Herni Serliyanti Lase, Eli Marlina Harahap, Nikmah Sari Hasibuan, (PAKAT: Jurnal Pengabdian Kepada Masyarakat, 2024)
This community service activity aims to improve poetry reading skills for Indonesian language students and teachers in secondary schools through training in vocal techniques, intonation, and expression in poetry reading. This training focuses on aspects of articulation clarity, voice dynamics, and understanding the meaning of poetry so that it can be conveyed more emotionally and communicatively. The methods used in this activity include lectures, demonstrations, and hands-on practice. Evaluation of the training results showed a significant improvement in the participants' ability to read poetry expressively. Thus, this training can be a strategic step in improving the appreciation of literature, especially poetry, in the educational environment.